Dual pedicle epiphyseal transfer for paediatric bony sarcoma reconstruction: Technique and review of outcomes. Issue 8 (August 2022) - Mughal, Maleeha; Rose, Victoria; Sindali, Katia; Farhadi, Jian; Havard, Heledd; Pollock, Robin; Roblin, Paul
Summary: Skeletal reconstruction after tumour resection in paediatric patients is challenging. The resultant reconstruction needs to meet the demands of graft incorporation as well as the potential for growth. The vascularised fibular epiphyseal transfer (VFET) offers the potential for both. We retrospectively reviewed eight paediatric patients treated with VFET after bony tumour resection. All patients underwent a dual pedicle transfer with the peroneal artery for the diaphyseal blood supply and the recurrent branch of the anterior tibial artery for the physis. This is the largest series in literature for dual pedicle transfers for bony reconstruction. We present our surgical technique and outcomes in terms of functional limb salvage and growth.